الاستثمار الأجنبي المباشر ودوره في تمويل التنمية الاقتصادية في الدول العربية - حيدر عفيف; بلول صابر; عماد أيهم (Latakia University Journal - Economic and Legal Sciences Series, 2019)
يتناول هذا البحث دور الاستثمار الأجنبي المباشر في تمويل التنمية الاقتصادية في الدول العربية كونّه يمثّل أحد أهمّ مصادر التمويل الخارجي. يهدف البحث إلى استعراض مقومات الاستثمار الأجنبي ومعوقاته في الدول العربية، وإيجاد آليات لتحفيز الاستثمار الأجنبي في هذه الدول. وقد توصل الباحث إلى أن حجم الاستثمارات الأجنبية في الدول العربية متواضع جداً، وأن دورها في التنمية الاقتصادية ما يزال ضعيفاً، ويعود ذلك إلى المناخ الاستثماري السائد الذي لم يكن مهيئاً لجذب هذه الاستثمارات، على الرغم من إدخال تعديلات عدّة على القوانين والتشريعات في الدول العربية معظمها بهدف تشجيع الاستثمارات الأجنبية المباشرة وجذبها. The research studies the role of direct foreign investment in funding the economic development in Arab countries being one of the most important sources of foreign funding. The research aims at illustrating the basics and the obstacles of foreign investment in these countries, and finding the mechanisms to stimulate the foreign investment. The research finds out that the amount of these investments is modest and their role in the economic development is still weak due to the current environment of investment which was not ready to attract these investments, in spite of the number of modifications on laws and legislations in most Arabic countries in order to encourage and attract the direct foreign investments.